Business-to-business brand management theory, research and executive case study exercises - Glynn, Mark S.; Woodside, Arch G. (Advances in business marketing and purchasing ;, 2009)
Providing broad and deep coverage, this volume focuses on sensemaking, decisions, actions, and evaluating outcomes relating to managing business-to-business brands including both product and service brands. This book goes well beyond basic marketing textbooks to provide extensive reviews of relevant studies, original research reports, and in-depth implications for B2B brand management issues. Each of the papers provides valuable brand management insights for managers. The chapters are original contributions by leading scholars and B2B brand managers; each chapter following the introductory chapter includes a brand management problem-exercise with a separate instructor's note.